Optimal management of distal ureteric strictures following renal transplantation: a systematic review. (7th March 2016) - Kwong, Justin; Schiefer, Danielle; Aboalsamh, Ghaleb; Archambault, Jason; Luke, Patrick P.; Sener, Alp
Summary: Our objective was to define optimal management of distal ureteric strictures following renal transplantation. A systematic review on PubMed identified 34 articles (385 patients). Primary endpoints were success rates and complications of specific primary and secondary treatments (following failure of primary treatment). Among primary treatments ( n = 303), the open approach had 85.4% success (95% CI 72.5–93.1) and the endourological approach had 64.3% success (95% CI 58.3–69.9). Among secondary treatments ( n = 82), the open approach had 93.1% success (95% CI 77.0–99.2) and the endourological approach had 75.5% success (95% CI 62.3–85.2). The most common primary open treatment was ureteric reimplantation ( n = 33, 81.8% success, 95% CI 65.2–91.8). The most common primary endourological treatment was dilation ( n = 133, 58.6% success, 95% CI 50.1–66.7). Fourteen complications, including death (4 weeks post‐op) and graft loss (12 days post‐op), followed endourological treatment. One complication followed open treatment. This is the first systematic review to examine the success rates and complications of specific treatments for distal ureteric strictures following renal transplantation. Our review indicates that open management has higher success rates and fewer complications than endourological management as a primary and secondary treatment for post‐transplant distal ureteric strictures. We also outline a post‐transplant ureteric stricture evaluation and treatment algorithm.